Factors influencing society to invest in unit trust: a case study in Shah Alam / Nur Razan Izzati Mohd Roslan - Mohd Roslan, Nur Razan Izzati (Academy of Contemporary Islamic Studies, 2018)
The Malaysian Capital Market is unique because it runs two types of capital market in the same time which is islamic and conventional. One of the component in Islamic Capital Market is unit trust. Unit Trust or mutual fund had played important role within the Malaysian Financial System as it can help boost investors wealth. The importance of Syariah Unit Trust can be seen from Financial Sector Blueprint 2011 - 2020, which is one of nine major areas highlighted in internalisation of islamic finance is to aim innovative islamic instrument financial by making more condusive environment for the mobilisation of higher volumes international islamic financial flows. The purpose of this research is to investigate the relationship between demographic profiles and level understanding of the respondants. This research also aims to identify the factor that influence society in investing. The results of the study shows that the factor that may influence investor to invest in unit trust is the product qualities. The study also found that the one who did not invest in unit trust is because they are confuse by variety of fund choices and did not approach by agents unit trust. Thus, it is hope that the study can add knowledge of the publics and give the fund companies some light to improve their marketing strategies.